PRESENÇA DO PAPILOMA VIRUS HUMANO EM CARCINOMA ANAL DE CÉLULAS ESCAMOSAS DE PACIENTES ATENDIDOS EM SÃO LUIS, MARANHÃO - Guimarães, Sulayne Janayna Araujo (2014)
The anal squamous cell carcinoma (SCCA) is rare, but its incidence has increased and have often been associated with human papilloma presence virus (HPV). Objective: In order to determine the prevalence of HPV infection in this histological variant, the study analyzed paraffin embedded samples of anal carcinoma in patients treated at the University Hospital of the Federal University of Maranhão (HUUFMA) and Maranhão Institute of Oncology Aldenora Bello (IMOAB) between 2001 and 2011. Methods: samples of anal cancer were included whose histological slides and paraffin blocks contained in patient files diagnosed in the Pathology Services IMOAB and HUUFMA and allowed confirmation of the diagnosis and evaluation of the proposed criteria this work. We collected demographic variables relating to the profile and clinical partner in the medical records and pathological reports of 27 patients. The tissue samples preserved in paraffin blocks were sent for DNA extraction using Qiagen column and Xylene Kit. The β-globin constitutive gene was amplified to certify the integrity of DNA in the samples. Later, there was amplification of HPV DNA by reaction technique Polymerase Chain (PCR) using the primer and SPF10 genotyping by reverse hybridization. Results: Among the patients evaluated, 74.07% were women; and 40.75% of the patients were aged between 42 and 52 years. Risk factors such as smoking (22.22%) and alcohol consumption (11.11%) were recorded in this group. Metastases were detected in 11.11% of cases with two cases of distant metastasis to the liver, rectum and vagina. HPV detection was at 81.48% of the positive samples. HPV16 was detected in 100% of the positive samples. High prevalence of HPV 11 was detected also in 11/27 (40.74%). Multiple infections showed 45.45% (10/22) of prevalence in the sample. Conclusion: Our results provide further evidence in support of the strong association of high-risk HPV infection in the development of anal SCC also highlighting a concern with late diagnosis and the need for monitoring and preventive measures for anal carcinoma.